Workers Knowledge about First Aids of Emergency Accidents at Industrial Sector of Al-Najaf City in Iraq - Tamim Yakoob AI-Sallami; Fatima Wanas Khudair (Indian Journal of Forensic Medicine & Toxicology, 2022)
Unintentional accidents and sudden illnesses are two of the most common causes of disability and death among workers, especially those under the age of forty . Using a simple random sample, twenty workers in the industrial workshops were randomly selected . A questionnaire consisting of two main groups was used. The result revealed that out of a total of 201 workshop workers included in the study, 59 (29.4%) of them had overall fair knowledge and 125 (62.2%) of the participating workers had poor knowledge, in addition to none having good knowledge. The results showed that only 17 (8.5%) of the workers had a positive attitude towards first aid. With regard to the relationship between the social and demographic data of the participants and their levels of knowledge, no an important correlation was not identified except for the monthly income, number of children and age, while with regard to workers’ attitudes towards first aid, residency in urban areas, years of experience, marital status, education level and receiving information about first aid showed significant correlation with their social relationships - demographic data.